TRANSFORMING SCHOOL CULTURE THROUGH CHARACTER EDUCATION: A CASE STUDY OF SD NEGERI 01 DORO - Ratna Kusuma Dewi; Harjito; Nurkolis (SOSIOEDUKASI, 2026)
This study explores the role of the school principal in transforming school culture through the implementation of character education at SD Negeri 01 Doro, a primary school in Doro District, Pekalongan Regency, Indonesia. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The research reveals that the school principal plays a pivotal role in integrating character education into the school's curriculum, extracurricular activities, and daily routines. Through strategic planning, the principal has successfully embedded values such as discipline, responsibility, and cooperation into the school's culture. The study highlights the importance of leadership in creating a positive school environment that supports character development, while also identifying challenges such as limited time and resources for teachers. The findings suggest that with consistent leadership and involvement of the entire school community, significant improvements in both student behavior and academic performance can be achieved. This case study provides valuable insights into how character education can be a powerful tool in reshaping school culture and enhancing the holistic development of students.